Використання рекурентних нейронних мереж для автоматичної діагностики раку легенів - Chapaliuk, Bohdan V.; Zaychenko, Yuriy P. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
The lung cancer is one of the most aggressive types of a cancer, which is the cause of the massive number of deaths worldwide. One of the methods to prevent the lung cancer death is to detect it on the earliest possible stage. Building an automated lung cancer detection system can help doctors with it. In the scope of this article we consider building a recurrent neural network, which can analyze lung CT scans. As a result, we have built a neural network, which consists of a convolution neural network, a recurrent neural network and an addition attention mechanism, which allows to reuse predefined information about possible malignant sections on the CT scan.